Understanding Western Culture Philosophy, Religion, Literature and Organizational Culture (Springer Singapore, 2018)
Promoting cultural understanding in a globalized world, this collection offers a new perspective on Western philosophy and religion through the voices of Chinese scholars. It examines the evolution of economic and political structures across the United States and the European Union, as well as key developments in various educational systems in the United Kingdom, Sweden, the US, France and Germany. As an interdisciplinary study situated at the intersection of sociology, history, culture and philosophy, this book re-examines pivotal structures and developments in Western countries and provides readers with a succinct yet effective way of mastering a deeper understanding of Western culture.